2017
DOI: 10.1038/s41598-017-01049-z
|View full text |Cite
|
Sign up to set email alerts
|

The GPR139 reference agonists 1a and 7c, and tryptophan and phenylalanine share a common binding site

Abstract: GPR139 is an orphan G protein-coupled receptor expressed in the brain, in particular in the habenula, hypothalamus and striatum. It has therefore been suggested that GPR139 is a possible target for metabolic disorders and Parkinson’s disease. Several surrogate agonist series have been published for GPR139. Two series published by Shi et al. and Dvorak et al. included agonists 1a and 7c respectively, with potencies in the ten-nanomolar range. Furthermore, Isberg et al. and Liu et al. have previously shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 58 publications
6
32
0
Order By: Relevance
“…Of note is Phe109Ala, which is one of the mutations that caused a complete loss of function to all four compounds. This result is consistent with an earlier report indicating Phe109 is highly important for these ligands ability to bind and mutation to alanine resulted in a complete loss of function . Nøhr et al also indicated Asn271 as another common binding site shared by these ligands and a mutation from a hydrophilic residue Asn to a hydrophobic residue Ala also resulted in a complete loss of function.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Of note is Phe109Ala, which is one of the mutations that caused a complete loss of function to all four compounds. This result is consistent with an earlier report indicating Phe109 is highly important for these ligands ability to bind and mutation to alanine resulted in a complete loss of function . Nøhr et al also indicated Asn271 as another common binding site shared by these ligands and a mutation from a hydrophilic residue Asn to a hydrophobic residue Ala also resulted in a complete loss of function.…”
Section: Resultssupporting
confidence: 92%
“…Lastly, the larger GPR139 agonists (TC-O 9311 and JNJ-63533054), also share a less buried hydrophobic pocket defined by residues Val76, Phe79, Ile104, Val83, and Ile80. This common binding site was also previously identified by Norh et al 15 Perhaps more importantly, we were able to identify mutations that rendered the receptor either more sensitive or less sensitive to the purported amino acid ligands. This should allow for the creation of transgenic animals that will require higher or lower levels of endogenous ligand to achieve activation, and enable more insight into the in vivo function of GPR139.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations